Structural change and women’s employment potential in Myanmar - Mueller, Valerie; Schmidt, Emily; Kirkleeng, Dylan (SAGE Publications, 2020)
We use the Integrated Household Living Conditions Survey to evaluate the extent women are included in Myanmar’s dynamic transformation process and the relative barriers that prohibit their inclusion between 2005 and 2010. Women play an active role in the labor force during a period of massive structural change. Their growing importance is substantiated by their increasing placement in manufacturing jobs near and away from home. Despite their increasing labor force participation, women’s engagement in manufacturing is negatively associated with household welfare. This may be a function of a gender pay gap or reflect households’ inability to substitute the labor of women to complete specific tasks related to household production. Future investments in surveys in Myanmar will improve our ability to identify which factors systematically provide an enabling environment for female labor participation, mobility, and improvements in well-being.